The Association Between French Veterinary Practice Characteristics and Their Revenues and Veterinarian's Time Use - Abdouttalib, Ikram; Ndiaye, Youba; Ferchiou, Ahmed; Raboisson, Didier; Lhermie, Guillaume (Frontiers in Veterinary Science, 2021)
Provision of healthcare by veterinarians consists of a blend of activities ensuring welfare for animals. It also contributes in the control of infectious diseases, and food safety. In general practices, most of the activities generate incomes for veterinarians, notably acts (consultations, surgery, etc.) and sales (drugs, pet food, etc.). Increased size of veterinary practices and the arrival corporate companies modifies the veterinary landscape in many countries. In a context of rapid growth of the companion animal health market, the question of the profitability of veterinary activities is relevant. Indeed, beyond a certain threshold, veterinarians may be tempted to leave behind food-producing animals acts and focus on companion animal’s acts, which are generally recognized to be more profitable and more attractive for new generations of veterinarians. A survey was conducted in French veterinary mixed practices, and a regression analysis was used to quantify the relationships between the turnover and the characteristics of veterinary practices, the time to perform veterinary acts and the characteristics of veterinarians. We found that the characteristics of veterinary practices are positively associated with the turnover and the price of acts, and an association between the status of veterinarians (associate, collaborator, employee) and the time required to perform companion animals and food producing animal’s acts. The present study is the first study showing the association between the characteristics of veterinary practices and the turnover, by investigating the price of veterinary acts and the time required.